ARTIFICIAL INTELLIGENCE AS A FACTOR IN THE TRANSFORMATION OF THE MODERN RUSSIAN LANGUAGE: LEXICAL, SYNTACTIC, AND PRAGMATIC ASPECTS - Dilnurakhon Sarvarjon qizi Murodova (International Journal of Literature and Language Studies, 2026)
The article presents a comprehensive analysis of the impact of artificial intelligence (AI) technologies, particularly large language models and neural machine translators, on the development of the modern Russian language. Based on a corpus analysis of Internet discourse, data from explanatory dictionaries of neologisms, and experimental observations of students’ speech behavior, the author identifies the main directions of linguistic change: the emergence of more than 50 new lexical units (prompt, neural network, tokenization, AI hallucination, etc.); syntactic convergence manifested in the spread of elliptical constructions and infinitive phrases typical of user prompts; and the stylistic homogenization of written language under the influence of standardized chatbot responses. The article also examines the risks of declining spelling literacy and critical thinking resulting from excessive reliance on AI assistants. In conclusion, a model of digital linguistic competence is proposed as an essential component of education in the era of generative AI. The article is intended for linguists, Russian language teachers, specialists in digital communication, and researchers in AI ethics.